1965
DOI: 10.1172/jci105193
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet Fibrinogen in the Reactions of Platelets to Thrombin*

Abstract: Washed human blood platelets contain a clottable protein that is similar to, if not identical with, plasma fibrinogen (1-4). After incubation with trypsin under appropriate conditions, platelets remain morphologically intact but no longer contain clottable protein (5). Trypsinized platelets, unlike normal platelets, are not aggregated by fresh serum or by a solution of thrombin and calcium chloride. When resuspended in plateletfree plasma or in a buffered solution of fibrinogen containing glucose, trypsinized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

1966
1966
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…The value for the radioactivity of these control specimens, about 100 cpm per 109 platelets, was subtracted from the value of each experimental result. 3 4 All determinations were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value for the radioactivity of these control specimens, about 100 cpm per 109 platelets, was subtracted from the value of each experimental result. 3 4 All determinations were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Thrombin, a proteolytic enzyme, is believed to cleave a fibrinogen-like constituent of the platelet membrane (4,5). This change in the platelet membrane renders it more permeable to serotonin, ADP, protein, and ions such as potassium and calcium (33,36), but the increased permeability may be relatively specific, since quite different proportions of various intracellular substances escape (33).…”
Section: Uu U)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although platelets are capable of high affinity uptake and stimulus-coupled secretion of serotonin, they have received little attention as a model secretary system because numerous studies have concluded that serotonin release by platelets is not dependent on extracellular Ca2+ and that intracellular stores provide what Ca2+ is needed for this purpose. In particular, thrombin (Morse, Jackson & Conley, 1965;Miller, Katz & Feinstein, 1975) and the Ca2+ ionophore A23187 (Massini & Luscher, 1974;White, Rao & Gerrard, 1974;Feinman & Detwiler, 1974;Feinstein & Fraser, 1975) both induce release by platelets incubated in a Ca2+-depleted medium (with added EDTA or EGTA), and this common observation has been used to support the above contention. While we have presented no evidence to refute the idea that a sarcoplasmic-reticulum-like organelle might function in platelets to provide Ca2+ for intracellular physiology and metabolism, we would suggest that the role of such an organelle may have been over-estimated and that given the appropriate circumstances, platelets do possess a release system which has a stringent requirement for extracellular Ca2+.…”
Section: Discussionmentioning
confidence: 93%
“…Interaction of plasminogen with platelets provides one mechanism by which platelets might participate in fibrinolysis. Early evidence in the literature suggested this possibility (1,3). We have recently demonstrated specific and saturable binding of plasminogen to platelets (4).…”
Section: Introductionmentioning
confidence: 90%